Kegiatan Stimulasi Motorik Kasar Anak Usia 2-3 Tahun di Taman Penitipan Anak - Santia, Reri; Jaya, Indra; Zulminiati, Zulminiati (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The purpose of this study was to find out how the gross motor stimulation activities of children aged 2-3 years in Taman Penitipan Anak Hikari Kids Club Padang. The research method used is descriptive with a qualitative approach. This research was carried out on the implementation of gross motor stimulation activities of children aged 2-3 years in Taman Penitipan Anak Hikari Kids Club Padang with informants/respondents were teachers who taught in the classroom TPA Aisyah. Data collection techniques in this study are observation, interview and documentation. Data analysis in the study was carried out in the form of descriptions namely words. The results of this study indicate that gross motor stimulation activities of children aged 2-3 years are well underway and refer to the child’s developmental needs. Planning is carried out in the form of RPPH in accordance with the theme indicators so that activities are structured and directed. Teacher use demonstration methods and media used by the media provided at school. And selected based on stimulation activities. Evaluation carried out on stimulation activities is in the form of assessment during the activity process and the teacher record important things.